1 Answer | Add Yours
To take the derivative of f(x), apply quotient rule which is `(u/v)' = (v*u' - u*v')/v^2` .
`u =6x^3-5` and `v=x^4`
Then,determine u' and v' .
`u'=18x^2` and `v'=4x^3`
And, plug-in u, v, u' and v' to the formula of quotient rule.
`f'(x) = (x^4*18x^2 - (6x^3-5)*4x^3)/(x^4)^2=(18x^6 - (24x^6-20x^3))/x^8`
To simplify further, factor out the GCF in the numerator.
`f'(x) = (2x^3(-3x^3+10))/x^8=(2x^3(10-3x^3))/x^8`
And cancel common factor.
Hence, the derivative of f(x) is `f'(x)= (2(10-3x^3))/x^5` .
We’ve answered 395,717 questions. We can answer yours, too.Ask a question